中国城市水电基础设施投资与管理 = Investment and management of urban water and electricity in China - 陈其春 Chen, Qichun (2008)
The supply of water and electricity in urban area is very important to urban development and residential living condition. The special feature of public good and scale of economy in water and electricity supply makes it a non-pure market commodity. How to determine the optimal quantity of supply of the water and electricity becomes a problem. In practice, it is worthwhile to find out the roles of enterprises and the government in supply of urban water and electricity. The purpose of this research is to use the theory of infrastructure investment to study the current case of China's water and electricity supply. Drawing on the successful experiences of the developed countries, I probe into the characteristics, price and demand, financing of construction and management, incentive mechanism, etc. in urban water and electricity supply. From the research, it is concluded that the investment in the public utility construction should be opened to the society and the price of water and electricity should be adjustable.